Induced changes in bioactive compounds of kailan-hybrid broccoli after innovative processing and storage - Ginés Benito Martínez-Hernández (Journal of Functional Foods, 2013)
The glucosinolates, sulforaphane, vitamin C and lutein content after several industrial cooking methods on the new kailan-hybrid broccoli and their changes during storage for 45 days at 4 °C were studied. Boiling and sous vide induced the highest glucosinolate loss (80%), while low pressure (LP) steaming, microwaving (MW) and sous vide-MW showed the lowest (40%) loss. Glucoraphanin was the most thermostable glucosinolate. Throughout their commercial life, microwaved and grilled samples showed a decrease in total glucosinolates. Generally, myrosinase activity was completely inhibited after cooking with undetected sulforaphane contents. The initial total vitamin C dropped by up to 58% after cooking and progressively decreased during storage, with sous vide-MW (92%) and microwaving (21%) showing the highest and lowest decrements, respectively. LP steaming and microwaving were the best industrial cooking methods for maintaining the glucosinolate and vitamin C contents, and enhancing up to 7.5-fold the initial lutein content.